Sleep disturbances and health-related quality of life in children with epilepsy: a caregiver survey - Wiesmüller, Luc; Strauch, Didare; Schönberger, Jan; San Antonio-Arce, Victoria; Bast, Thomas; Schubert-Bast, Susanne; Syrbe, Steffen; Jacobs, Julia; Klotz, Kerstin Alexandra (Epilepsy & behavior, 2025)
Introduction - Sleep disorders are common in patients with epilepsy. In adults, evidence suggests reduced sleep quality and its negative impact on health-related quality of life (HRQoL). However, data on large pediatric cohorts remain limited. This study investigates the relationship between epilepsy and subjective sleep quality as well as its association with HRQoL in a large cohort of children with epilepsy (CWE). - Material and Methods - A parental online survey was conducted for CWE up to 15 years. Biographical and medical information was collected and standardized questionnaires were administered to assess parent reported sleep quality (Children’s Sleep Habit Questionnaire), and HRQoL (KINDL®-questionnaire). - Results - A total of 304 CWE (52.3 % male) were surveyed, with a median age of 7 years (range 1-15). Seizure frequency varied from daily (25 %) to less than once per year (24.7 %). Antiseizure medication (ASM) was used in 93.8 %, with 30 % receiving ≥ 3 ASMs. Comorbidities, such as autism or ADHD, were reported in 179 children (58.9 %). The mean sleep disturbance score was 54.8 (SD 9.4), with 290 children (95.4 %) scoring above 41, indicating impaired sleep. CWE with both, daytime and nocturnal seizures had worse sleep quality compared to those with daytime seizures only (p = 0.027). The use of sedative medications, like clobazam, was associated with impaired sleep quality (p = 0.025) and shorter sleep duration (p = 0.005). - Conclusion - CWE experience poorer sleep quality compared to children without epilepsy, especially when nocturnal seizures are present, regardless of the number of ASMs or presence of comorbidities. In CWE, impaired sleep correlates with lower HRQoL.
Online verfügbar 5 August 2025, Version des Artikels 5 August 2025
Gesehen am 16.12.2025